Pantun as a Character Education Media in Building the Profile of Pancasila Students in the Multicultural Era - Martono Martono; Iwan Ramadhan; Jagad Aditya Dewantara (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study aims to examine the fundamental role of Pantun as a medium of communication and cultural expression that embodies values of character education. It specifically seeks to identify how these values can be integrated into building the Profile of Pancasila Students in the multicultural era. The research employed a qualitative descriptive method. Data were collected from Pantun delivered by Mr. Mastur, a rhyme speaker and palace guard of the Almukarramah Palace. The poems reflecting character education values were classified, analyzed, and interpreted through a hermeneutic approach, particularly Ricoeur’s interpretive model. The findings reveal that Pantun contains a variety of character education values, including: patriotism and truth, responsibility, discipline, and independence, trust, respect and politeness, affection, attention, and hard work, self-confidence, creativity, and perseverance, justice and leadership, kindness and humility, and tolerance and love for peace. These values represent noble moral messages and cultural identity that are highly relevant to the realization of the Pancasila Student Profile in a multicultural context. Pantun serves not only as a literary and cultural heritage of the Malay community but also as an effective medium for instilling character education. Its integration into educational practices enriches the cultural and multicultural dimensions of learning, contributing to the holistic development of student character. The study highlights the importance of local cultural wisdom, particularly Pantun, in strengthening the Pancasila Student Profile. Future research is recommended to expand the analysis of Pantun across regions and multicultural settings, and to develop pedagogical models that implement Pantun-based character education in formal and informal environments.